2017
DOI: 10.1111/pde.13237
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Follow‐Up of Lymphatic Malformations in Children Treated with Sildenafil

Abstract: This is the first report of long-term follow-up of pediatric LM patients treated with sildenafil. Our findings suggest that sildenafil is beneficial for the symptomatic treatment of LMs. Additional analysis on the role of sildenafil as adjuvant therapy is necessary to optimize the use of this medication in the management of complex LMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…All patients experienced sustained improvement over time with use of PDE-5i. Duration of continuous PDE-5i for 2 patients has significantly exceeded treatment durations previously reported for pediatric LM 1,2,3,4,5,6 . PDE-5i lead to smooth muscle relaxation in blood vessels causing dilation and may similarly affect lymphatic vessel smooth muscle.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…All patients experienced sustained improvement over time with use of PDE-5i. Duration of continuous PDE-5i for 2 patients has significantly exceeded treatment durations previously reported for pediatric LM 1,2,3,4,5,6 . PDE-5i lead to smooth muscle relaxation in blood vessels causing dilation and may similarly affect lymphatic vessel smooth muscle.…”
Section: Discussionmentioning
confidence: 77%
“…Key words: lymphatic malformation, sildenafil, phosphodiesterase-5 inhibitor Author conflict of interest: none Lymphatic malformations (LM) are rare congenital anomalies 1,2 and are notoriously refractory to treatment. Conventional treatment options are invasive and include surgical resection, debulking and sclerotherapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 The LMs of children treated with sildenafil for pulmonary hypertension improved significantly, and subsequent studies showed the treatment was effective in improving clinical symptoms, softening masses, and reducing the size of the lesions in patients with LMs. [8][9][10][11][12][13] In recent years, basic research has revealed that lymphatic endothelial cell (LEC) somatic gene mutations in LMs lead to persistent activation of the PI3K/AKT/mTOR pathway, which is an essential cause of developing LMs. Sirolimus, an inhibitor of mTOR, has been shown in numerous studies to significantly improve the imaging and clinical symptoms of patients with LMs.…”
Section: Introductionmentioning
confidence: 99%
“…The drug has been approved for the treatment of pulmonary hypertension in adults, and its application to LMs began in 2012 with a report published in the New England Journal of Medicine 7 . The LMs of children treated with sildenafil for pulmonary hypertension improved significantly, and subsequent studies showed the treatment was effective in improving clinical symptoms, softening masses, and reducing the size of the lesions in patients with LMs 8–13 . In recent years, basic research has revealed that lymphatic endothelial cell (LEC) somatic gene mutations in LMs lead to persistent activation of the PI3K/AKT/mTOR pathway, which is an essential cause of developing LMs.…”
Section: Introductionmentioning
confidence: 99%